Nuclear Radiations and their Application - Singh, B. P. (SCHOOL SCIENCE, 2023)
Atoms are tiny building blocks of matter that make up everything. The central part of the atom is called nucleus and the electrons revolve around it. The nucleus has protons that are positively charged while the neutrons are neutral. Electrons revolve around the nucleus in different orbits. In the year 1909, a famous scientist Ernest Rutherford, performed an experiment where alpha scattering on thin gold foil was studied and showed that almost entire mass of the atom is concentrated at its centre called the nucleus. We know that the nucleus is made up of protons and neutrons and these are compactly packed together because of strong forces. When some nuclei are not stable, they change and give off particles or energy. This helps them become stable. The time it takes for half of the atoms to convert into new more stable ones is called half-life. Marie Curie found out about radioactivity. She showed that there are three main types of radiation: alpha, beta and gamma. These types have many applications in medicine and other fields. In medicine, radio-isotopes help us to see inside the body. Technetium-99m is an example and has many applications in medical sciences. Radiation is also used to keep the food safe and clean by the process called food irradiation. Sometimes, people think radiation is not good for food but this is not the case. Caution needs to be taken to irradiate the food with controlled amount of radiation as prescribed by regulatory bodies. There are always risks with different activities we do, like making electricity from oil, coal, solar and nuclear energy. While we can’t get rid of all risks, we try to make them as small as possible. The nuclear industry follows strict safety rules to reduce risks. Nuclear technology, in general, helps in medicine, industry, agriculture, energy and research. We must understand that nothing we do is completely risk-free but we want the benefits from nuclear technology to be higher than the possible problems. We need to educate people about the benefits of the nuclear radiations and use it safely for the benefit of mankind.